The Car Hacker's Handbook. Issue 4 (April 2016) - Unknown
Abstract : It's probably going to be a while before hacking motor vehicles is a standard component in a penetration test, but car hacking has definitely arrived. So if you're curious about how it's done, this is the place to start.